Strategi Komunikasi dalam Pembinaan Prajurit Remaja Baru TNI AD di Satuan Kerja Hubdam XIV/Hasanuddin 2021 - Asriani Alimuddin; Asrul Nur Iman; Jusran Jusran (Journal of Government Insight, 2022)
This paper aims to find out how the communication strategy of developing soldiers to strengthen the character of the new adolescent soldiers of the TNI AD Hubdam XIV/Hasanuddin as well as the supporting and inhibiting factors of the communication strategy of developing soldiers towards strengthening the character of the adolescent soldiers of the TNI AD Hubdam XIV/Hasanuddin. This study uses a qualitative approach with a descriptive type of research. The results showed that the communication strategy applied in strengthening the character of the new teenage soldiers of the TNI AD Hubdam XIV/Hasanuddin was in accordance with the steps of preparing the communication strategy expressed by (Anwar Arifin, 2015) which began with the stage of getting to know the audience, compiling messages, choosing the appropriate method. used. The supporting factor in the communication strategy of developing soldiers for strengthening the character of the youth soldiers of the TNI AD Hubdam XIV/Hasanuddin is the positive perception of the coaches and senior soldiers towards the new soldiers who are believed to be able to carry out their duties and work well and can fill the positions left by the soldiers. seniors as a form of regeneration. Another supporting factor is the enthusiasm of the new teenage soldiers in receiving the coaching materials so as to create a conducive and comfortable situation where every material or message conveyed by the coaches can be received and responded to properly